Historical epidemiology of hepatitis C virus in select countries—volume 4. (4th November 2017) - Maaroufi, A.; Vince, A.; Himatt, S. M.; Mohamed, R.; Fung, J.; Opare‐Sem, O.; Workneh, A.; Njouom, R.; Al ghazzawi, I.; Abdulla, M.; Kaliaskarova, K. S.; Owusu‐Ofori, S.; et al.
Summary: Due to the introduction of newer, more efficacious treatment options, there is a pressing need for policy makers and public health officials to develop or adapt national hepatitis C virus (HCV) control strategies to the changing epidemiological landscape. To do so, detailed, country‐specific data are needed to characterize the burden of chronic HCV infection. In this study of 17 countries, a literature review of published and unpublished data on HCV prevalence, viraemia, genotype, age and gender distribution, liver transplants and diagnosis and treatment rates was conducted, and inputs were validated by expert consensus in each country. Viraemic prevalence in this study ranged from 0.2% in Hong Kong to 2.4% in Taiwan, while the largest viraemic populations were in Nigeria (2 597 000 cases) and Taiwan (569 000 cases). Diagnosis, treatment and liver transplant rates varied widely across the countries included in this analysis, as did the availability of reliable data. Addressing data gaps will be critical for the development of future strategies to manage and minimize the disease burden of hepatitis C.